VD_FINDINFO HC / 2014 / 627 vom 7. Juli 2014 - VD Tribunal cantonal (2014)
REVENU HYPOTHÉTIQUE, BONUS, MESURE PROVISIONNELLE, OBLIGATION D'ENTRETIEN | 176 al. 1 CC, 308 al. 1 let. b CPC (CH), 312 al. 1 CPC (CH)